How COVID-19-related crime infected Europe during 2020 (Europol, 2020)
While the COVID-19 pandemic1 is first and foremost a global public health crisis, it has also proven to have a significant and potentially long-lasting impact on the serious and organised crime and terrorism landscape in Europe as well as the ability of Member State law enforcement authorities to counter security threats.